Development of Paper-Based Biosensors for Point of Care Diagnostics - รักทอง ภัทรสุดา; ภัทรมานนท์ รินา (KKU Science Journal, 2013)
The natural paper products are used in various fields including diagnostics by applying the properties to match with the interface of biosensors, the highly effective device for analyzing biological samples. Paper-based biosensors are developed as a tool for analyze and diagnose a wide range of biological compounds by modifying the recognition element and transducer that can be combined for qualitative or quantitative analysis. They are also portable and are able to use outside the laboratory and for the field study. Some paper-based biosensors have been engineered for patients to read the result on their own at home. The diagnosis can be reported by computer software or mobile applications. Paper-based biosensor might replace the original equipments that are large, expensive, and imported from abroad, and requires an expert to read the analysis. Paper-based biosensors are also useful for point of care diagnosis system that can be accessed in the remote or isolated regions for proper healthcare.